Administration of Phyllanthus niruri to control IMNV (myonecrosis infectious virus) infection white shrimp Litopenaeus vannamei - Sukenda .; Sri Nuryati; Isni Rahmatika Sari (Jurnal Akuakultur Indonesia)
ABSTRACT